PERBEDAAN KECEPATAN WAKTU REAKSI RANGSANG CAHAYA SEBELUM DAN SESUDAH TERPAPAR FAKTOR LINGKUNGAN FISIK PADA PEKERJA INDUSTRI PENGECORAN LOGAM PT. INGENYST SEMARANG - Ulfa Nurullita (Universitas Muhammadiyah Semarang, 2007)
Background: Work activity is usually done in an environment or situation which leads to addecl burflen of workers physically and spiritually. Physical factor of added burden as the effect of dominant work environtruentin metal faundry industry is heat pressure, noise, and lighting. Workload and environment factor affect on workers' convenience and health problem, so that it can increase workload itself, accelerate fatigue andsubjective complaint, as well as decrease work productivity. One of the fatigue measurements is by calculating reaction time toward some stimulus. Method: Location chosen is department of melting ancl making of concrei iron and curved iron which have the same workload. The amount of samples is 47 workers with age inclusion criteria of 40 years old maximally, male, I workhours each day, more than a week of work perioi, hating no hearth and kidney problem, diabetes mellitus, hypertension, hypotension, anemia, ancl asthma, having no lijuor habit and sport. This Qpe of research is the quasi experiment with one group pre antl post test tlesign. Reaition time rapidity is measured before ancl after working with Rection Timer 77, heat pressure is measured with Questemp 10, whereas noise is measured with sound level meter. Result of the research shows that the average of reaction time before working is 253,2 ml second, it is lower if compared to the average of reaction time after working, that is, 290,7 ml second. ln conclusion, there is difference of light stimulating reaction time for workers in deportment of melting and making of concrete iron and curyed iron between before antl after working (p:0,00 1). Reaction time rapidity is increasing after workers deal with work environment either hear pressure, lighting, or noise.Keyword: reaction time rapidiqt, physical factors, metal faundry industry